Geological CO2 Storage Characterization The Key to Deploying Clean Fossil Energy Technology - Surdam, Ronald C.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This book investigates geological CO2 storage and its role in greenhouse gas emissions reduction, enhanced oil recovery, and environmentally responsible use of fossil fuels. Written for energy/environmental regulators at every level of government (federal, state, etc.), scientists/academics, representatives from the power and fossil energy sectors, NGOs, and other interested parties, this book uses the characterization of the Rock Springs Uplift site in Wyoming as an integrated case study to illustrate the application of geological CO2 storage science, principles, and theory in a real-world scenario. This book investigates geological CO2 storage and its role in greenhouse gas emissions reduction, enhanced oil recovery, and environmentally responsible use of fossil fuels. Written for energy/environmental regulators at every level of government (federal, state, etc.), scientists/academics, representatives from the power and fossil energy sectors, NGOs, and other interested parties, this book uses the characterization of the Rock Springs Uplift site in Wyoming as an integrated case study to illustrate the application of geological CO2 storage science, principles, and theory in a real-world scenario. Ronald C. Surdam has authored 200 articles in refereed scientific journals and books and has given more than 300 invited lectures. He founded and directed the Institute for Energy Research and directed the Enhanced Oil Recovery Institute at the University of Wyoming, and has consulted for many international energy and mineral exploration corporations. Over the past 45 years, Surdam has focused on oil and gas exploration, oil shale and trona depositional systems, coal and zeolite deposits in the Rocky Mountain Laramide basins of Wyoming and other states, and anomalously pressured natural gas accumulations and geological CO2 storage around the world. He has served the State of Wyoming in numerous capacities, most recently as Director of the Wyoming State Geological Survey. Currently, as Director of the University of Wyoming Carbon Management Institute and Principal Investigator of the Wyoming Carbon Underground Storage Project ($20 million), Surdam is helping lead the effort to accomplish commercial geological CO2 sequestration in the Rocky Mountain region. As a visiting professor at three Chinese universities, he is also assisting with carbon storage in the Shaanxi and Shanxi provinces of China.
Keywords: Geography; Geology, economic; Hydraulic engineering; Earth Sciences; Environmental Science and Engineering; Geotechnical Engineering & Applied Earth Sciences; Geoengineering, Foundations, Hydraulics; Economic Geology; Earth System Sciences; Fossil Fuels (incl. Carbon Capture).